Microwave aided scalable synthesis of sulfur, nitrogen co-doped few-layered graphene material for high-performance supercapacitors. (10th December 2020) - Rotte, Naresh Kumar; Naresh, Vangapally; Muduli, Sadananda; Reddy, Venu; Srikanth, V.V.S.; Martha, Surendra K.
Highlights: S, N -FLG synthesized from the acid treated graphite flakes by microwave irradiation. S, N-FLG electrodes show the specific capacitance of 298 F g −1 at 1 A g −1 . fS, N-FLG electrode sustains 95 % of capacitance retention after 10000 cycles at 1 A g −1 . An energy density of 15 Wh kg −1 exhibited at a power density of 300 W kg −1 . Achieved capacitance is due to formation of N-S-H bonds and S, N co-doping in graphene. Abstract: Doping with heteroatoms has become an approach for improving the electrochemical performance of few-layered graphene. In this work, Sulfur-nitrogen co-doped few-layered graphene synthesized from the graphite flakes acid treated with H2 SO4 and HNO3 followed by microwave irradiation. Sulfur-nitrogen co-doped few-layered graphene consists of less than 15 graphene layers with a high degree of graphitization. The supercapacitor exhibited a specific energy density of 15 Wh kg −1 at a power density of 300 W kg −1 at room temperature in aqueous electrolyte. The S, N-FLG electrodes show the specific capacitance of 298 F g −1 at a current density of 1 A g −1 and stable over 10, 000 continuous charge-discharge cycles with 95% capacitance retention at 1 A g −1 . The obtained capacitance is due to maximum utilization of few-layered graphene sheets, highest intrinsic surface capacitance due to the synergetic effect of the formation of N-S-H hydrogen bonds and S, N co-doping in graphene aromatic rings. Graphical abstract: Image, graphical abstract